Percobaan Pengolahan Air Limbah Yang Mengandung Bahan Aktif MIPC Dengan Proses Penggumpalan Dan Pengendapan - Siti N T Hidayati (Jurnal Kimia dan Kemasan, 1989)
Experiment has been carried out to waste water containing MIPC which is treated by floculation and sedimentation process. It seen thet treatment time, type of treated material and the concentration of floculant influence the treatment result. In this case the floculant and sedimentation treatment method gave a better result.